1997
DOI: 10.1159/000006738
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the P Wave with Signal Averaging to Assess the Risk of Atrial Fibrillation after Coronary Artery Bypass Surgery

Abstract: P wave signal averaging was performed in 91 consecutive patients undergoing coronary artery bypass grafting to detect patients at risk of postoperative atrial fibrillation (AF). Sixteen patients (17.5%) developed AF after surgery. The P wave duration on the signal-averaged electrocardiogram (ECG) and on surface ECG was prolonged in AF patients compared to others (respectively 141 ± 12 vs. 132 ± 12 ms and 124 ± 9 vs. 113 ± 9 ms). The root mean square voltages (RMS) of the total P wave were not different between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 14 publications
0
18
0
1
Order By: Relevance
“…Age is the variable most consistently associated with post-CABG AFIB (1,4,9,11,13,16,(23)(24)(25)(26)(27). In this study, age provided the greatest contribution to the correct prediction of AFIB in the logistic regression model (14% of a total of 25% cumulative percent correct prediction).…”
Section: Discussion Preoperative Predictive Characteristicsmentioning
confidence: 50%
See 2 more Smart Citations
“…Age is the variable most consistently associated with post-CABG AFIB (1,4,9,11,13,16,(23)(24)(25)(26)(27). In this study, age provided the greatest contribution to the correct prediction of AFIB in the logistic regression model (14% of a total of 25% cumulative percent correct prediction).…”
Section: Discussion Preoperative Predictive Characteristicsmentioning
confidence: 50%
“…Neither study related a cumulative percentage of prediction for the model. Age was also found to be the best predictor of AFIB in studies where signal-averaged ECG data were utilized in the model (16,23). When Frost et al (16) performed regression analysis on a variety of variables in a study utilizing P-wave duration and morphology on signal-averaged ECG, they noted that only increased age (>60 yrs) and increased body weight (> 80 kg) were independent predictors of AFIB, for a cumulative positive prediction of 37%.…”
Section: Regression Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…23 Changes in P-wave morphology indicative of atrial dilatation or hypertrophy are useful, 23,24 but their accuracy as predictors of imminent or even eventual fibrillation is variable. Patient populations with postoperative AF have been used to study the utility of signal-averaged P waves, [25][26][27][28][29] and here an increase in P-wave duration has been a reasonable indicator of risk. 25 However, other studies have demonstrated that nonspecific variables, such as gender and age, are equally or more accurate markers.…”
Section: Noninvasive Predictors Of Afmentioning
confidence: 99%
“…In this context, P-wave signalaveraged electrocardiography proved to be a noninvasive, low-cost, easily performed and reproducible method; therefore, it has been widely used in the evaluation and stratification of the risk of atrial fibrillation [16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%